2007
DOI: 10.1111/j.1440-1746.2007.04941.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between expression of leptin and clinicopathological features and prognosis in patients with gastric cancer

Abstract: The expression of leptin in the tissue of gastric cancer was significantly associated with tumor histology, Borrmann classification, lymph node metastasis and stage of gastric cancer. In patients with poorly differentiated gastric cancer, a poor prognosis was found in those with a strong expression of leptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 30 publications
(36 reference statements)
4
36
4
1
Order By: Relevance
“…Poorly cohesive carcinomas belong to the diffuse type according to the Lauren classification. By analyzing 61 gastric cancer cases, Zhao et al observed a significant association between leptin expression and vascular endothelial growth factor (VEGF) expression [105]. Further, leptin expression in these gastric cancer tissues was significantly associated with histology, Borrmann classification, lymph node metastasis and stage.…”
Section: Leptin and Tumor Behavior Of The Gastrointestinal Tractmentioning
confidence: 99%
“…Poorly cohesive carcinomas belong to the diffuse type according to the Lauren classification. By analyzing 61 gastric cancer cases, Zhao et al observed a significant association between leptin expression and vascular endothelial growth factor (VEGF) expression [105]. Further, leptin expression in these gastric cancer tissues was significantly associated with histology, Borrmann classification, lymph node metastasis and stage.…”
Section: Leptin and Tumor Behavior Of The Gastrointestinal Tractmentioning
confidence: 99%
“…In patients with OGC, a number of primary and secondary causes of reduced dietary intake are at work simultaneously, including dysphagia (McKernan et al, 2008), early satiety (Davis et al, 2006), chronic nausea (McKernan et al, 2008), alterations in circulating neuroendocrine hormones (e.g., ghrelin (Isomoto et al, 2005) and leptin (Huang et al, 2005;Zhao et al, 2007)), hypogeusia/hyposmia (Plata-Salaman, 2000), and cytokine-induced central anorexia (Plata-Salaman, 2001;Turrin et al, 2004). Assuming that MIC-1 may be a modulator of appetite in humans, the complex constellation of additional factors also controlling food intake may explain why plasma MIC-1 concentrations did not correlate with nutritional status in this study.…”
Section: Crp (Mg Lmentioning
confidence: 99%
“…We thought that the main reason for these results were different histopathological subgroups and chemotherapy regimens. Not only lung carcinoma, but also leptin shows a prognostic value for the overall survival rate in patients with gastric adenocarcinoma (17), hepatocellular carcinoma (18) and colorectal adenocarcinoma (19). Although Duru (20) et al found high serum leptin levels in advanced stage of lung NSCLC compared to healthy subjects, we did not fi nd any correlation between serum leptin levels and lung cancer stage or histological subtype.…”
Section: Discussionmentioning
confidence: 99%